2005
DOI: 10.1182/blood-2004-09-3387
|View full text |Cite
|
Sign up to set email alerts
|

IgG antibodies that recognize epitope Gly40-Arg43 in domain I of β2–glycoprotein I cause LAC, and their presence correlates strongly with thrombosis

Abstract: Anti

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
347
6
9

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 370 publications
(373 citation statements)
references
References 28 publications
(30 reference statements)
11
347
6
9
Order By: Relevance
“…The bulk of the evidence favors aPL binding immunodominant epitopes located within the N-terminal (domain I) (13)(14)(15). The ability of anti-␤ 2 GPI antibodies purified from patients with autoimmune disease to bind domain I of ␤ 2 GPI has been shown to be strongly correlated with the occurrence of thrombosis in those patients (16). Studies on expressed mutants of whole ␤ 2 GPI with incorporated single-point substitution mutations within domain I identified the residues G40 and R43 as being important in conferring binding to aPL (14,17).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The bulk of the evidence favors aPL binding immunodominant epitopes located within the N-terminal (domain I) (13)(14)(15). The ability of anti-␤ 2 GPI antibodies purified from patients with autoimmune disease to bind domain I of ␤ 2 GPI has been shown to be strongly correlated with the occurrence of thrombosis in those patients (16). Studies on expressed mutants of whole ␤ 2 GPI with incorporated single-point substitution mutations within domain I identified the residues G40 and R43 as being important in conferring binding to aPL (14,17).…”
mentioning
confidence: 99%
“…Studies on expressed mutants of whole ␤ 2 GPI with incorporated single-point substitution mutations within domain I identified the residues G40 and R43 as being important in conferring binding to aPL (14,17). De Laat et al (16) identified a population of anti-␤ 2 GPI antibodies derived from patients with thrombosis that bind domain I exclusively. This binding was considerably reduced by the introduction of mutations G40E and R43G.…”
mentioning
confidence: 99%
“…Isolated LAC was not a risk factor for deep vein thrombosis in the Leiden thrombophilia study [17]. Further, it was shown that antibodies directed against a specific epitope (Gly40-Arg43) in the domain I of b 2 GPI (anti domain I antibodies) are responsible for LAC activity as well as thrombosis [18]. The significance of b 2 GPI independent LAC activity or aCL antibodies is under scrutiny.…”
Section: Issues With the Current Diagnostic Criteria Of Aps And Propomentioning
confidence: 99%
“…It has been repeatedly observed invitro prolongation coagulation test with positivity antibodies against DI [3,8].…”
Section: Journal Of Hematology and Thromboembolic Diseasesmentioning
confidence: 99%
“…Evidence of the pathogenicity of anti-DI antibodies comes from both in-vitro and in-vivo studies. First, anti-DI antibodies were repeatedly observed to induce in-vitro prolongation of clotting time [3][4][5][6][7][8].…”
Section: Journal Of Hematology and Thromboembolic Diseasesmentioning
confidence: 99%